Case report of a delayed iatrogenic Pipkin type III femoral head fracture-dislocation. Issue 4 (28th January 2022) - Li, Qin-Wen; Zhou, Cai-Sheng; Li, Yu-Peng
Abstract: Rationale: Pipkin III femoral head fracture dislocation (FHFD) is rarely observed in clinical practice, and its outcome is alarming. A considerable proportion of Pipkin III fractures result from repeated or forceful closed reduction of an irreducible FHFD. Pipkin type III fractures pose a therapeutic challenge. Most patients underwent total hip arthroplasty. Patient concerns: A 34-year-old man experienced high-energy trauma to the left hip from a terrible traffic accident. Radiography and computed tomography (CT) at the local hospital revealed a left posterior FHFD. Emergency close reduction of the hip was performed.48 hours later, the patient was transferred to our institution. New radiography and CT examinations demonstrated an iatrogenic femoral neck fracture (FNF) associated with FHFD. In addition, a right talar fracture was observed. Diagnosis: Pipkin III fracture combined with contralateral talar fracture. Interventions: Considering his Pipkin fracture classification (Pipkin Type-III) and the time to surgery after his injury (>48 hours), the patient underwent left total hip arthroplasty uneventfully, followed by below-ankle plaster cast immobilization for his right ankle. Outcomes: At the 6-month follow-up, the patient was able to walk pain-free, and plain radiographs were satisfactory, with no evidence of heterotopic ossification or osteonecrosis of the talus. Lessons: Before emergency closed reduction, early recognition of the unique characteristics of an irreducible FHFD is essential to avoid iatrogenic femoral neck fracture.